Effect of cutting fluid pressure on machining of AISI 304 performances / Zainal Arifin Selamat and Mohd Razali Muhamad - Selamat, Zainal Arifin; Muhamad, Mohd Razali (2008)
This thesis presents the effect of cutting fluid pressure on the cutting performance. The cutting fluid is being used in metal cutting to optimize the process of machining operation. It has a significant role on shop floor productivity, tool life and quality of work. The objective of the study is to investigate the effect of cutting fluid pressure and machine parameter on the tool wear, tool life, chip formation and surface roughness on the process of metal cutting. The stainless steel AISI 304 and AI2O3 coated cemented carbide insert were used as a work piece material and cutting tool respectively. The experiment was being carried out on CNC turning machine with 2 axes movements using the different nozzle sizes. The cutting variables including the surface roughness, tool wears and tool failure modes were considered in this research. The effect of the cutting parameters including the cutting time, cutting speed, and depth of cut were investigated.